Konsep Kearifan Tempatan Menurut Perspektif Hukum Islam: The Concept of Local Wisdom in The Islamic Law Perspective - Rosele, Muhammad Ikhlas; Ali, Abdul Karim (Jurnal Fiqh, 2019)
Local wisdom is a widely used concept in social science. It is a concept that describes the roles of identity of a region and society or a small group that affect their life systems. However, the position of this concept in Islamic law is still vague. Hence, this study analyzes the position of local wisdom according to Islamic law perspectives. This study conducted using a qualitative approach by using full library data. The inductive, deductive and comparative methods of analysis are used to obtain the necessary results. The study found that the concept of local wisdom exists and is acknowledged in Islamic law. In addition, the concept of local wisdom is not necessarily understood as ‘urf.